Factors Associated with Loss to Follow-Up in Pediatric Concussion Patients after Initial Visit: A Retrospective Study at a Concussion Clinic - Emilia Núñez-Peña, MD; Ryan P. Kelly, BS; Santiago Campos, MD; Maria C. Diaz, MD; Pamela A. Castillo, MD; Shivangi Kataria, MSAB; Alexia M. Perez, MD; Maria Dolores Beletanga, MD; Alcy R. Torres, MD (Journal of Pediatrics: Clinical Practice)
Objective: The objective of this retrospective study is to identify factors associated with loss to follow-up for postconcussion clearance in pediatric patients by comparing loss to follow-up and full clearance patients. Study design: This retrospective single-center cohort study analyzed 140 consecutive patients at a pediatric concussion clinic of a safety-net hospital for loss to follow-up, defined as not achieving clearance at last appointment. Univariate and multivariate regression models were fit on variables of interest, including demographic, mechanism and severity of concussion, and characteristics of the first evaluation postconcussion and follow-up management. Results: Of the sample, 40% (n = 56) achieved clearance and 60% (n = 84) were lost to follow-up. Median age was 15 (IQR 11-17), with male predominance (60.7%). Living with a biological parent (OR = 0.145, 95% CI = 0.028-0.760) and sports involvement (OR = 0.256, 95% CI = 0.092-0.764) were protective factors, while being 10 years old or older (OR = 13.466, 95% CI = 2.792-64.958) and attending 2 or fewer follow-up appointments (OR = 19.027, 95% CI = 4.991-72.533) were risk factors for loss to follow-up. No significant differences were found between sex, race, driving distance, type of insurance, and mechanism of injury. Conclusions: Living with a biological parent and involvement in sports showed to be protective factors for loss to follow-up. Age at time of concussion and number of appointments were risk factors. A “golden window” of 2 appointments was identified, highlighting the need of a strong rapport and engagement in shared decision-making. Future directions include prospective studies implementing strategies targeting adolescents and building a strong patient-provider relationship.